Immunogenicity of meningococcal polysaccharide ACWY vaccine in primary immunized or revaccinated adults. (20th September 2018) - Ferlito, C; Biselli, R; Cattaruzza, M S; Teloni, R; Mariotti, S; Tomao, E; Salerno, G; Peragallo, M S; Lulli, P; Caporuscio, S; Autore, A; Bizzarro, G; et al.
Summary: Meningococcal polysaccharide (Men-Ps) vaccine immunogenicity following either primary immunization or revaccination in adults was evaluated. The study population consisted of subjects who have received tetravalent Men-Ps vaccine once (group 1) or at least twice, with a 2–6 dose range (group 2). Human leucocyte antigen (HLA)-typing was performed by polymerase chain reaction and specific immunoglobulin (Ig)G was measured by enzyme-linked immunosorbent assay. Nine months post-immunization, the percentages of individuals with levels of anti-Men-Ps IgG ≥ 2 µg/ml were comparable in both groups, with the exception of anti-Men-PsW135 IgG, which were significantly higher in group 2. The percentage of subjects doubling IgG levels at 9 months was significantly higher in group 1. The high baseline anti-Men-Ps antibody levels negatively influenced the response to revaccination, suggesting a feedback control of specific IgG. The calculated durability of anti-Men-Ps IgG was 2·5–4·5 years, depending on the Men-Ps, following a single vaccine dose. No interference by other vaccinations nor HLA alleles association with immune response were observed. This study confirms that Men-Ps vaccine in adults is immunogenic, even when administered repeatedly, and underlines the vaccine suitability for large-scale adult immunization programmes that the higher costs of conjugate vaccines may limit in developing countries. Graphical Abstract: